Rural–urban disparities in knowledge, behaviors, and mental health during COVID-19 pandemic: A community-based cross-sectional survey. Issue 13 (2nd April 2021) - Zhang, Jianmei; Zhu, Liang; Li, Simin; Huang, Jing; Ye, Zhiyu; Wei, Quan; Du, Chunping
Abstract : Abstract: To examine the knowledge level, behaviors, and psychological status of the Chinese population during the COVID-19 pandemic, and to explore the differences between urban and rural areas. We carried out a cross-sectional survey of the knowledge, behaviors related to COVID-19, and mental health in a probability sample of 3001 community residents in 30 provinces or districts across China from February 16–23, 2020. Convenience sampling and a snowball sampling were adopted. We used General Anxiety Disorder (GAD), the 9-item Patient Health Questionnaire (PHQ-9), and knowledge and behaviors questionnaire of community residents regarding COVID-19 designed by us to investigate the psychological status, disease-related knowledge, and the behavior of Chinese urban and rural residents during the pandemic. The average score of anxiety and depression among urban residents was 9.15 and 11.25, respectively, while the figures in rural areas were 8.69 and 10.57, respectively. There was a statistically significant difference in the levels of anxiety ( P  < .01) and depression ( P  < .01). Urban participants reported significantly higher levels of knowledge regarding COVID-19 in all aspects (transmission, prevention measures, symptoms of infection, treatment, and prognosis) ( P  < .01), compared to their rural counterparts. While a majority of respondents in urban areas obtained knowledge through WeChat, other apps, and the Internet ( P  < .01), residents in rural areas accessed information through interactions with the community ( P  < .01). Urban residents fared well in exchanging knowledge about COVID-19 and advising others to take preventive measures ( P  < .01), but fared poorly in advising people to visit a hospital if they displayed symptoms of the disease, compared to rural residents ( P  < .01). Regression analysis with behavior showed that being female (OR = 2.106, 95%CI = 1.259–3.522), aged 18 ⩽ age < 65 (OR = 4.059, 95%CI = 2.166–7.607), being satisfied with the precautions taken by the community (OR = 2.594, 95%CI = 1.485–4.530), disinfecting public facilities in the community (OR = 2.342, 95%CI = 1.206–4.547), having knowledge of transmission modes (OR = 3.987, 95%CI: 2.039, 7.798), symptoms (OR = 2.045, 95%CI = 1.054–4.003), and outcomes (OR = 2.740, 95%CI = 1.513–4.962) of COVID-19, and not having anxiety symptoms (OR = 2.578, 95%CI = 1.127–5.901) were positively associated with affirmative behavior in urban areas. Being married (OR = 4.960, 95%CI = 2.608–9.434), being satisfied with the precautions taken by the community (OR = 2.484, 95%CI = 1.315–4.691), screening to ensure face mask wearing before entering the community (OR = 8.809, 95%CI = 2.649–19.294), and having knowledge about precautions (OR = 4.886, 95%CI = 2.604–9.167) and outcomes (OR = 2.657, 95%CI = 1.309–5.391) were positively associated with acceptable conduct in rural areas. The status of anxiety and depression among urban residents was more severe compared to those living in rural areas. There was a difference in being positively associated with constructive behaviors between rural and urban areas.